Contribution of Latin–American Scientists to the Study of the Magnetosphere of the Earth. a Review - Stepanova, M (Elsevier Ltd, 2016)
Since the very beginning of the space era, Latin–American scientists have been contributing to the understanding of the magnetosphere of the Earth. This review summarizes some significant contributions in this field with emphasis on results obtained during the last decade. Special attention is paid to most important topics of the magnetosphere of the Earth such as geomagnetic storms and substorms and possible relations between them, interplanetary origin of storms, role of turbulent processes in the magnetosphere dynamics, and analysis of the dynamics of the magnetosphere as a complex self-organized non-linear system. © 2016 COSPAR